The Role of Low Molecular Weight Heparins for Venous Thromboembolism Prevention in Medical Patients—What Is New in 2019? - Haas, Sylvia (Hämostaseologie, 2019)
Low molecular weight heparins and fondaparinux have been the cornerstones for prevention of venous thromboembolism (VTE) in acutely ill medical patients for almost two decades. Guidelines recommend the use of these parenteral anticoagulants for 6 to 14 days but advise against extended-duration thromboprophylaxis after hospital discharge because no compelling scientific evidence has been provided for pharmacological prophylaxis beyond hospital stay. Five large randomized clinical trials, one with low molecular weight heparin and four with nonvitamin K antagonist oral anticoagulants, have failed to show significant clinically relevant benefit in this indication. Obviously, the development of VTE is more complex in medical patients than in patients undergoing major surgical procedures. Thus, it can be expected that guideline recommendations for VTE prevention with low molecular weight heparins or fondaparinux in medical patients will remain unchanged in 2019.
Keywords: VTE prevention; medical patients; low molecular weight heparins; nonvitamin K antagonist oral anticoagulants